Pengaruh Work Life Balance, Stress Kerja Dan Etika Kerja Islam Terhadap Kinerja Karyawan Pasca Pandemi Covid – 19 di Bank Muamalat KCU Medan Baru - Rizky, Muhammad; Nawawi, M.; Inayah, Nurul (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This exploration plans to figure out how Islamic hard working attitudes, work pressure, and balance between serious and fun activities impact representative execution at Bank Muamalat KCU Medan Baru after the Coronavirus pandemic. This examination is a kind of survey research using a quantitative system. This investigation data was obtained from 34 respondents using an inside and out examination system. Opinion polls are used in the process of gathering information. The data checking procedure in this investigation is genuine checking with the assistance of the SPSS transformation 23.0 program. The exploration's findings indicate that representative implementation is influenced by a combination of work pressure and a hard-work attitude, as well as a balance between fun and serious activities. This is shown by the likely eventual outcomes of the T test and F test.Work pressure tcount (1.082) ttable (1.697) tcount (6.437) ttable (1.697) tcount (0.894) ttable (1.697) tcount (0.894) ttable (1.697) tcount (0.894) ttable (1.697) tcount (0.894) ttable (1.697) ttable (1.697) tcount (0.894) ttable (1.697) ttable (1.697) In the interim the F test produces Fcount (20.086) > Ftable (4.160) and a sig worth of 0.000 < 0.05.